Behind enemy lines - Davis, John; Moore, John; Veloz, David; Penn, Zak; Twentieth Century-Fox Film Corporation (United States : Twentieth Century Fox, 2004)
Navy flight navigator Lt. Burnett and his pilot are shot down over Bosnia during a routine reconaissance mission after seeing something the Serbian forces didn't want them to see. Once on the ground, deep inside enemy territory, the chase is on as they are tracked by rebel forces who want to make sure they are dead. Meanwhile back on the aircraft carrier, the commander, who wants to mount a rescue mission, must play political games to make it happen
Title from title screen
Director of photography, Brendan Galvin ; editor, Paul Martin Smith ; music composer, Don Davis ; costume designer, George L. Little ; production designer, Nathan Crowley
Casts: Owen Wilson, Gene Hackman, Gabriel Macht, Joaquim de Almeida, David Keith, Olek Krupa, Vladimir Mashkov, Charles Malik Whitfield
With Mandarin and Malay subtitles
Keywords: Naval reconnaissance -- Drama; Adventure films; Feature films; Yugoslav War, 1991-1995 -- Drama; United States. -- Navy -- Drama